Talbinah as food and medicine: a review - Nurul Hafizah Mohd Nor; Nabila Syafiqa Abdul Rani; Farah Ayuni Mohd Hatta; Wan Nasyrudin Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Talbinah is a carbohydrate-rich, nutritious food that contains various important macro- and micronutrients. This so-called barley porridge or barley water is a type of Prophetic food and one of the favourite foods of Prophet Muhammad (peace be upon him). In one of the hadiths in the Book of Medicine (Book 76) of Sahih al-Bukhari, Prophet Muhammad (peace be upon him) mentioned that this traditional food is a source of nourishment that helps the people who consume it to calm their hearts and emotions. Although this food has been traditionally consumed since ancient times, there is a dearth of scientific study that has been done on this food. Therefore, this article aimed to investigate the therapeutic effect of talbinah specifically on emotional problems. The study was conducted by focusing mainly on the hadith book Sahih al-Bukhari, in which the hadiths with the word ‘talbinah’ occurs were reviewed and selected. Then, the scientific data on the selected hadiths were searched in four academic search engines, i.e, Google Scholar, PubMed, Medline and Science Direct were analysed regardless of the year of publication to investigate the therapeutic effectiveness of talbinah in alleviating stress, anxiety, depression and other emotional problems. The results showed that talbinah may provide mental health benefits for people, although there are still a limited number of studies on this nutritious food. More in vitro and in vivo studies are needed, in addition to other types of experimental studies on talbinah.